Enhancing Maritime Education and Operations through IT, IoT, and Computer-Based Learning - Panderaja Soritua Sijabat; Rosna Yuherlina Siahaan; April Gunawan Malau (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to examine how Information Technology (IT), the Internet of Things (IoT), and Computer-Based Learning (CBL) are integrated into maritime operations and education, and to identify the structural barriers that constrain their full implementation. Despite the accelerating pace of digital transformation in the maritime sector — driven by IMO emissions regulations, smart port development, and Industry 4.0 — no prior qualitative study has simultaneously examined IT/IoT integration in operations and CBL adoption in education within a single analytical framework targeting Indonesian maritime professionals and educators, representing the specific gap this study addresses. A qualitative research design was employed, drawing on semi-structured interviews and focus group discussions with 33 participants: 8 maritime industry professionals (entrepreneurs, vessel officers, and port managers), 12 maritime lecturers and trainers, and 13 recent graduates from Indonesian maritime polytechnic institutions. Data were analyzed through a systematic six-phase thematic analysis procedure (Braun & Clarke, 2006) with intercoder verification (Cohen's Kappa κ = 0.82). Three themes emerged: high IT/IoT awareness constrained by infrastructure and standardization deficits; CBL effectiveness hampered by resource limitations and instructor capacity gaps; and industry-education collaboration as necessary but structurally underdeveloped. The study's principal contribution is a dual-domain analytical framework connecting operational IT/IoT integration barriers with CBL implementation conditions — demonstrating that both are driven by the same root cause of inadequate governance coordination between maritime industry stakeholders and educational institutions, a finding not previously articulated in the maritime technology education literature.